(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article examines the types and forms of English diplomatic relations, highlighting their significance in fostering international cooperation and promoting the UK's strategic interests. The analysis categorizes diplomatic relations into bilateral, multilateral, economic, and cultural exchanges. It further explores the various forms of diplomacy, including embassies, consulates, treaties, and joint projects. By employing a qualitative approach that reviews academic literature and official documents, the study reveals how these diplomatic frameworks enable the UK to maintain a strong global presence and effectively address contemporary challenges. Understanding these dynamics is essential for appreciating the complexities of modern diplomacy and international relations.